2012
DOI: 10.1002/chem.201102637
|View full text |Cite
|
Sign up to set email alerts
|

Photomagnetism of a sym‐cis‐Dithiocyanato Iron(II) Complex with a Tetradentate N,N′‐Bis(2‐pyridylmethyl)1,2‐ethanediamine Ligand

Abstract: A comprehensive study of the magnetic and photomagnetic behaviors of cis-[Fe(picen)(NCS)(2) ] (picen = N,N'-bis(2-pyridylmethyl)1,2-ethanediamine) was carried out. The spin-equilibration was extremely slow in the vicinity of the thermal spin-transition. When the cooling speed was slower than 0.1 K  min(-1), this complex was characterized by an abrupt thermal spin-transition at about 70 K. Measurement of the kinetics in the range 60-70 K was performed to approach the quasi-static hysteresis loop. At low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 56 publications
4
35
1
Order By: Relevance
“…This overlap results in unusual shapes of the thermal hysteresis due to the kinetic effects, as shown in Figure 4. It also completes the magnetic and photomagnetic studies performed on cis-[Fe(picen)(NCS) 2 ] (picen= N,N'-bis(2-pyridylmethyl)1,2-ethanediamine) [47], which also belongs to the same class, with an extremely slow spin equilibration in the vicinity of the thermal spin transition. Several examples in the literature could be also regarded in the light of overlapping SCO regions, such as the 2D coordination network [Fe(bbtr) 3 ](ClO 4 ) 2 doped with Zn(II) [48].…”
Section: -supporting
confidence: 60%
“…This overlap results in unusual shapes of the thermal hysteresis due to the kinetic effects, as shown in Figure 4. It also completes the magnetic and photomagnetic studies performed on cis-[Fe(picen)(NCS) 2 ] (picen= N,N'-bis(2-pyridylmethyl)1,2-ethanediamine) [47], which also belongs to the same class, with an extremely slow spin equilibration in the vicinity of the thermal spin transition. Several examples in the literature could be also regarded in the light of overlapping SCO regions, such as the 2D coordination network [Fe(bbtr) 3 ](ClO 4 ) 2 doped with Zn(II) [48].…”
Section: -supporting
confidence: 60%
“…Thermal equilibration can be sometimes "frozen out" at cryogenic temperatures [8][9][10][11][12], so that minority states can be enriched as meta-stable species through irradiation with light or via rapid freezing. The former effect was coined as light-induced excited spin-state trapping, LIESST, whereas thermal induced excited spin-state trapping, TIESST, has been established as an alternative method for kinetic stabilization via rapid freezing [9]. Around ambient temperature, however, the exchange reactions are very rapid, leading to randomizing spin states within a few nanoseconds in most iron(II) complexes [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies provide ample information about photochemical processes in the solid state, be it about light-induced chemical transformations (Chaudhary et al, 2017), structures of exited states (Raithby, 2015;Hatcher & Raithby, 2013) or spin-crossover phase transitions (Lé tard et al, 2012). To the best of our knowledge in the vast majority of such studies, especially those related to timeresolved crystallography, synchrotron sources were used (Fullagar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One of the first such devices was designed more than a decade ago at Durham University (Thompson et al, 2004) and was successfully used for a number of years [some results are reported by Lé tard et al (2012)]. The setup consisted of a laser and a set of mirrors mounted on the 2 arm of a Bruker three-circle diffractometer equipped with a Helix (Oxford Cryosystems) cryostat.…”
Section: Introductionmentioning
confidence: 99%